Cell Division and morphogenesis in Staphylococcus aureus - Pereira, Ana Raquel Ramos (2021)
The cell shape is such a distinctive characteristic of bacteria that it has been used extensively for their classification. In most bacteria, cell shape is sustained by peptidoglycan, a macromolecular polymer that surrounds the cell conferring mechanical strength and protecting the cell from lysing from high turgor pressure. The ability of bacteria to faithfully maintain morphology in a population and to pass it on to the next generation suggests the existence of molecular mechanisms that control morphogenesis. (...)